2021
DOI: 10.7759/cureus.13070
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Serum Ceruloplasmin Levels as a Biomarker for Oxidative Stress in Patients With Diabetic Retinopathy

Abstract: BackgroundElevated serum ceruloplasmin is a biomarker for oxidative stress. Diabetes mellitus (DM) is known to be a state of oxidative stress which causes complications of DM including diabetic retinopathy (DR). The role of ceruloplasmin in DR is still unclear. MethodsNinety patients of DM were included as cases and after evaluation sub-grouped as those with no DR, nonproliferative DR (NPDR) and proliferative DR (PDR). Serum ceruloplasmin levels were tested in all cases as well as in equal numbers of age and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
1
3
0
Order By: Relevance
“…In RNaseq analysis of the retina, an increased Cp expression (Figure I) was observed, which was improved by nCUR+INS and INS groups, while CUR and nCUR had little to no effect. These observations align well with the literature, where the Cp level was significantly elevated in DR patients . The transcriptomic analysis of the retina further revealed the regulation of cytosolic iron–sulfur cluster biogenesis (Figure J) and nonheme Fe-containing protein pirin (Figure K).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…In RNaseq analysis of the retina, an increased Cp expression (Figure I) was observed, which was improved by nCUR+INS and INS groups, while CUR and nCUR had little to no effect. These observations align well with the literature, where the Cp level was significantly elevated in DR patients . The transcriptomic analysis of the retina further revealed the regulation of cytosolic iron–sulfur cluster biogenesis (Figure J) and nonheme Fe-containing protein pirin (Figure K).…”
Section: Resultssupporting
confidence: 90%
“…These observations align well with the literature, where the Cp level was significantly elevated in DR patients. 38 The transcriptomic analysis of the retina further revealed the regulation of cytosolic iron−sulfur cluster biogenesis (Figure 7J) and nonheme Fe-containing protein pirin (Figure 7K). A significantly lower expression of Ciao 1 and pirin was observed in the diabetic group, and all the treatments neutralized this effect in ciao1 but not pirin expression.…”
Section: Resultsmentioning
confidence: 96%
“…elevated glycation accompanied with an altered lipid profile in T2DM causes enhanced generation of this enzyme which could be used as possible biomarker for identifying accelerated glycation and atherosclerosis 23 . Another study revealed a highly significant increase in CP concentration in sera of patients with T2DM 24 ; There is metabolic and OS in uncontrolled diabetes 25 , CP is thought to be a scavenger so its levels increase.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast to decreased GSH, there was an elevation in the concentration of non-enzymatic antioxidant CP in PTSD individuals when compared to healthy control groups. Ceruloplasmin has an essential role as a protective agent against oxidative stress and in the control of lipid oxidation [ 46 ]. Therefore, serum CP levels in PTSD individuals are elevated to overcome the elevation in MDA levels in order to protect the body from lipid peroxidation.…”
Section: Discussionmentioning
confidence: 99%